Protein or Amino Acid Deprivation Differentially Regulates the Hepatic Forkhead Box Protein A (FOXA) Genes Through an Activating Transcription Factor-4–Independent Pathway - Su, Nan (2009)
The FOXA (forkhead box A) proteins (FOXA1, FOXA2, and FOXA3) play a critical role in the development of the liver, and they also regulate metabolism in adult hepatic tissue. The liver responds to changes in nutrient availability by initiating a number of stress signaling pathways. The present studies demonstrated that in mouse dams fed a low-protein diet hepatic expression of FOXA2 and FOXA3 messenger RNA, but not FOXA1, was induced. Conversely, fetal liver did not exhibit this regulation. Amino acid deprivation of HepG2 hepatoma cells also enhanced transcription from the FOXA2 and FOXA3 genes. In contrast, endoplasmic reticulum stress inhibited the expression of FOXA1, only slightly induced FOXA2, and had no effect on FOXA3. The FOXA2 and FOXA3 messenger RNA induction by amino acid deprivation did not require activating transcription factor 4, a critical component of the conventional amino acid response (AAR) pathway, but their induction was partially dependent on CCAAT/enhancer-binding protein β. Simultaneous knockdown of both FOXA2 and FOXA3 by small interfering RNA did not affect the activation of other amino acid responsive genes, suggesting that the FOXA proteins are not required for the known AAR pathway. Collectively, the results document that the hepatic FOXA family of genes are differentially regulated by amino acid availability.